2009
DOI: 10.1177/1091581809354342
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Acute Toxicology Study of Surfactant-Stabilized Ultrasound Contrast Agents in Adult Rats

Abstract: Gas-filled microbubbles are used as contrast agents in diagnostic ultrasound imaging. A preclinical, acute toxicity study of 2 surfactant-stabilized ultrasound contrast agents (ST68 and ST44) was conducted. Subjects were 104 Sprague-Dawley rats (experimental doses, 0.1, 0.2, 0.8, and 1.0 mL/kg; control, 1.0 mL/kg saline) that were studied for 14 days after contrast; clinical signs, weight, blood, and urine were evaluated. Histopathology was performed following euthanasia. Of the 40 animals receiving ST44, 4 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This estimate is well below the tolerance of peripheral venous endothelial cells in animal models (reported as 820 mOsm/kg for 8 h (Kuwahara et al, 1998). Additionally, toxicity studies in rats injected with a similar surfactant-shelled microbubble using Span 60 and Tween 80 without the glucose cryoprotectant have shown the microbubbles to be well tolerated (Forsberg et al, 2010), and replacement of Tween with water soluble vitamin E is expected to further improve this tolerability. While removal of Span would further improve tolerability, the stability of the bubble shell is dependent on the presence of at least one non-water soluble surfactant (results unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate is well below the tolerance of peripheral venous endothelial cells in animal models (reported as 820 mOsm/kg for 8 h (Kuwahara et al, 1998). Additionally, toxicity studies in rats injected with a similar surfactant-shelled microbubble using Span 60 and Tween 80 without the glucose cryoprotectant have shown the microbubbles to be well tolerated (Forsberg et al, 2010), and replacement of Tween with water soluble vitamin E is expected to further improve this tolerability. While removal of Span would further improve tolerability, the stability of the bubble shell is dependent on the presence of at least one non-water soluble surfactant (results unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has studied the fabrication, characterization, and in vivo imaging potential of surfactant-stabilized microbubbles extensively (Wheatley and Singhal, 1995; Forsberg et al, 1997, 1999; Basude et al, 2000; Basude and Wheatley, 2001). The low toxicity of microbubbles, combined with the ability to control microbubble size, provides a safe and easily customizable platform for delivery of bioactive gases (Forsberg et al, 2010; Wheatley et al, 2006). Finally, a recent method of freeze-drying these particles under vacuum (Solis et al, 2010) allows the nascent bubble to be preserved for extended periods of time and resuspended with a desired gas.…”
Section: Introductionmentioning
confidence: 99%
“…The mean diameter of PFB@PLLA nanoparticle is ~350 nm (Figure D), which is determined by DLS. Additionally, the toxicity studies in rats injected with a similar PLLA‐shelled microbubbles have shown the good biocompatibility . Therefore, our synthesized PFB@PLLA nanoparticles are safe for US imaging.…”
Section: Resultsmentioning
confidence: 73%
“…Additionally, the toxicity studies in rats injected with a similar PLLA-shelled microbubbles have shown the good biocompatibility. [14][15][16] Therefore, our synthesized PFB@PLLA nanoparticles are safe for US imaging.…”
Section: Resultsmentioning
confidence: 97%
“…This dose was well below amounts indicated in toxicology reports of sonographic contrast agent injections in monkeys. 16,17 During the working phase, all subjects were intubated during contrast agent injections for fear of contrast agent reactions. However, all subjects tolerated the injections well and had a quick recovery after sedation; therefore, intubation was not used for contrast-enhanced sonography in the recovery phase.…”
Section: Discussionmentioning
confidence: 99%